Cocoa butter and related compounds - Garti, Nissim, 1945-; Widlak, Neil R. (AOCS Press, 2012)
This book covers the progress of the last 10 years of studies on cocoa butter. Descriptions of several aspects, including physical characteristics such as rheology, hardness, melt profiles, etc., studied by new and advanced techniques are included. Similarly, the polymorphism of cocoa butter is reconsidered in light of studies done by synchrotron DSC, FTIR, and SAXS techniques. These data are complemented by new understandings on the cause of the crystallization and transitions of the polymorphs. Other aspects such as the effect of minor components, emulsifiers, and other fats are discussed in great detail in this book.